The Role of Volume, Conductivity, Scatter Changes of Neutrophils and Monocytes in Diagnosis of Megaloblastic Anemia - Adiga, Deepa Sowkur Anandarama; Saha, Debarshi; G, Karthick R; M, Vishnu Priya; Rao, Purnima S; Suresh, Pooja K (Annals of Pathology and Laboratory Medicine, 2020)
Background: Megaloblastic anemias are macrocytic normochromic anemia with mean corpuscular volume (MCV) of 100 fl-140 fl and caused by deficiency of either cobalamin (vitamin B12) or folate. However, increased MCV is not specific for megaloblastic anemia, nor is Vitamin B12 assay by chemiluminescence. We undertook this study to evaluate the possible role of Volume, Conductivity and Scatter (VCS) of WBCs derived from standard hematology analyzer to indicate megaloblastic anemia. Methods: We performed a case control study comparing data of 60 patients with low serum vitamin B12 or folate levels with 60 healthy volunteers. Comparison of the volume, conductivity and scatter parameters for neutrophils and monocytes of cases and control were done. Result: The mean neutrophil volume of cases (158.37±18.13fl) was significantly higher (p= 0.0001) compared to controls (141.26±4.22fl). Similarly, mean monocyte volume of cases (183.34±16.90fl) was significantly (p=0.0001) higher compared to controls (166.55±8.66fl). The difference in the mean conductivity of both neutrophils and monocytes between cases and controls were insignificant (p=0.43). Conclusion: Our study suggests analysis of VCS parameters for neutrophils and monocytes was a simple and objective method that substantiates the existence of subclinical deficiency of vitamin B 12 and folate with fair degree of certainty.